Visible-light driven heterojunction photocatalysts for water splitting – a critical review. Issue 3 (5th March 2015) - Moniz, Savio J. A.; Shevlin, Stephen A.; Martin, David James; Guo, Zheng-Xiao; Tang, Junwang
<x xml:space="preserve">Abstract</x> We summarise current state-of-the-art efficient visible-light driven heterojunction water splitting photo(electro)catalysts and describe how theoretical modelling of electronic structures at interfaces can explain their functionality.